Evaluation of genetic counseling among cystic fibrosis carriers, Michigan Newborn Screening1. Issue 2 (20th November 2012) - Kleyn, Mary J.; Langbo, Carrie; Abdulhamid, Ibrahim; Adamski, Craig R.; Allan, Catherine; Carmany, Erin P.; Gregoire‐Bottex, M. Myrtha; Homnick, Douglas; Schuen, John; Nasr, Samya Z.
Abstract Objective A quality improvement (QI) strategy to improve the rate of genetic counseling (GC) services was initiated in cystic fibrosis (CF) care Center E in 2010. This statewide study was conducted to determine: (1) GC rates before and after implementation of the QI strategy at Center E; (2) characteristics associated with not receiving GC; and (3) topic areas addressed during GC. Methods The retrospective study included 1, 097 CF carriers born from 2008 to 2011 identified through Michigan's Newborn Screening Program. Rate of GC services was determined for Center E and the other four CF centers before and after the QI change. Bivariate and multivariable logistic regression was used to determine associations between select characteristics and not receiving GC. Topic areas discussed during GC sessions were assessed using frequency tables. Results Rate of GC services in Center E increased from 23% in 2008–2010 to 91% in 2011, while at the other centers approximately 92% received GC services across those years. In 2008–2010, being seen at Center E and black race were significantly associated with increased likelihood of not receiving GC services in adjusted analyses. In 2011, neither characteristic was associated with receipt of GC. Of 16 target topic areas, all were discussed in 85% of GC sessions. Conclusions Implementing a QI strategy of providing sweat test results at the GC appointment within Center E resulted in more CF carriers receiving comprehensive GC services. Center‐specific procedure differences should be assessed to increase rate of GC services following a positive CF newborn screen. Pediatr Pulmonol. 2013; 48:123–129. © 2012 Wiley Periodicals, Inc.